PEMODELAN GEOLOGI DAN ESTIMASI SUMBER DAYA BATUBARA DI PIT â€œHMGâ€, TAMBANG BATUBARA BANKO BARAT, SUMATRA SELATAN: GEOLOGICAL MODELLING AND COAL RESOURCE ESTIMATION IN THE â€œHMGâ€ PIT, WEST BANKO COAL MINE, SOUTH SUMATRA - Adithya Ramadhani Hasibuan; Juniarto, Reinaldi; Nurdrajat; Reza Mohammad Ganjar Gani; Dicky Muslim; M. Dwiki Satrio (Buletin Sumber Daya Geologi, 2020)
Indonesia is a country that has a lot of coal deposits, and one of the largest deposits is in Sumatra Island. The Bukit Asam coal mine has had a long history beginning with the Dutch colonial period. Administratively, location of the studied area is located in the area of Bukit Asam coal mine, Tanjung Enim area, Muara Enim Regency, South Sumatra Province. This paper provides the 2D and 3D geological modelling to estimate coal resources in the â€œHMGâ€ PIT of West Banko Coal Mine. Forty-eight exploratory drill holes data from PT Bukit Asam were used in this study. There were reanalysed and reinterpreted to identify coal characteristics, correlate coal seams, and compile to create subsurface geological models. In an effort to determine coal resources in this area, there were some analytical techniques (criteria or parameter), including geological complexity analysis, coal quality distribution analysis, subsurface mapping to observe the geometry of coal seam distribution and making geological models from the results of drilling activities. The studied objects are seams A1, A2, B1, B2, and C with rank of high volatile B bituminous based on the ASTM Classification. The coal seams distribution shows relatively southeast-northwest trends. Resources classification or estimation in this paper is based on SNI 5015 : 2011, in which the study area is included in the geological complexity of simple geological groups with the distance of inferred resource information 1,000<Xâ‰¤ 1,500m, designated 500<Xâ‰¤1,000m, and measured Xâ‰¤500m. From geological modelling and the Circular Method, estimated coal seam A1 resource is 28,543,893 tons, A2 seam is 31,199,799 tons, seam B1 is 38,638,462 tons, seam B2 is 15,790,222 tons, and seam C is 40,913,153 tons. The total coal resources are 155,085,529 tons.